Tell Me More: Effectiveness in developing communication Skill - Shanker, Jayanthi; Hishan, Sanil S (International Journal of Psychosocial Rehabilitation, 2020)
Tell Me What is a solution that includes modules with various subjects and contexts to enable students to improve their English-language skills. The research measured Tell Me More's efficacy in strengthening the management capabilities for interventions to enhance system execution. The study participants are 108 graduates, both paramedical and non-paramedical. A self-made method was used; mathematical methods include Weighted Mean and T-Test use version 18 of PASW. Tell Me More is considered to be highly effective in developing users 'listening and speaking skills while increasing the ability to write and learn. There is no significant difference in the effectiveness of TELLL ME MORE between the responses of paramedical and non-paramedical students. People deny that by utilizing Ask Me More, they face issues and disagreements. English teachers are expected to analyze and use lessons and units related to writing and reading to improve students 'skills in these areas. Different or modified functions may be done to supplement the existing modules. The routine training or updating course on Tell Me More apps should be retained to insure that the courseware is used efficiently.